Low-Density Lipoprotein Cholesterol and Mortality Risk in Elderly Patients Undergoing Valve Replacement Surgery: A Propensity Score Matching Analysis - Li, Han-biao; Fu, Bing-qi; Tan, Tong; Li, Xiao-hua; Wang, Shou-hong; Wei, Xue-biao; Wang, Zhong-hua (Frontiers in Nutrition, 2022)
Background: The prognostic value of low density lipoprotein cholesterol (LDL-C) in elderly patients is controversial. This study aimed to elucidate the relationship between the preoperative LDL-C and adverse outcomes in elderly patients undergoing valve replacement surgery (VRS). Methods: A total of 2552 aged patients (age ≥ 60 years) undergoing VRS were retrospectively recruited and divided into two groups according to LDL-C level on admission: low LDL-C (<70mg/dL, n=205) and high LDL-C groups (≥ 70mg/dL, n=2347). The association between the preoperative LDL-C with in-hospital and one-year mortality was evaluated by propensity score matching analysis and multivariate analysis. Results: The mean age was 65 ± 4 years and 1263 (49.5%) were men. Patients in the low LDL-C group were significantly older (65.9±4.6 vs. 64.9±4.1, p=0.002), with more male (65.4% vs. 48.1%, p<0.001), higher ALT (21.0 vs. 19.0, p=0.001), lower serum albumin (35.3±4.6 vs. 37.1±4.1, p<0.001), higher serum creatinine (92.2±38.2 vs.84.6±26.1, p=0.006), lower lymphocyte count (1.7±0.7 vs. 1.9±0.6, p<0.001), lower hemoglobin (121.9±22.3 vs. 130.2±16.5, p<0.001), lower platelet count (171.3±64.3 vs. 187.7±58.7, p<0.001), lower prognostic nutrition index (44.0±6.2 vs. 46.7±5.8, p<0.001) and more severe tricuspid regurgitation (33.7% vs. 25.1%, p=0.008). The rates of in-hospital death (11.2% vs. 3.7%, p<0.001) and major adverse clinical events (17.6% vs. 9.6%, p<0.001) were significantly higher in the low LDL-C group. The cumulative one-year death rate was significantly higher in the low LDL-C group (Log-Rank=16.6, p<0.001). After matching analysis and multivariate analysis, no association between LDL-C level and adverse outcomes was detected (all p>0.05). Conclusion: Our study did not support the negative relationship between LDL-C level and mortality risk in elderly patients undergoing VRS.